Health Literacy Level and Quality of Life among Post-Partum Mothers - Ulfah, Maria; Fauziah, Anny (Jurnal Kesehatan, 2024)
Pregnancy and childbirth are natural physiological processes that involve tremendous changes in the mother's physiology, anatomy, and psychology. Apart from that, pregnancy and birth can disrupt physical and mental health, so it has a significant impact on the quality of life of post-partum mothers. Poor quality of life in post-partum mothers becomes, which affects the health of the mother and baby. This study aims to analyze the relationship between health literacy and the quality of life of post-partum mothers in the Bandung Health Center, Tegal City. The research method uses quantitative with a cross-sectional approach. The population of this study was all post-partum mothers who gave birth in June – July 2023 in the Bandung Community Health Center area, Tegal City. The total sample was 59 post-partum mothers. Data collection using the HLS-EU-Q16 and Post-partum Quality of Life (PQOL) questionnaires. In the adequate health literacy category, 43 respondents (72.9%), followed by the problematic health literacy category 15 respondents (25.4%) and low literacy level 1 respondent (1.7%). In addition, of the respondents with a good quality of life, 57 respondents (96.6%) had a good quality of life, and 2 respondents (3.4%) had a low quality of life. Based on the chi-square test, there is a relationship between health literacy and the quality of life of post-partum mothers, which shows a significant relationship with a significance level of p=0.05). This research concludes that good health literacy gives post-partum mothers a good quality of life so they can care for their newborn babies.